Role of gamma‐delta (γδ) T cells in autoimmunity. Issue 2 (10th December 2014) - Paul, Sourav; Shilpi,; Lal, Girdhari
Abstract : Review on cellular and molecular cross‐talk between γδ T cells and adaptive immune cells in the pathogenesis of autoimmune diseases. Abstract : γδ T cells represent a small population of overall T lymphocytes (0.5–5%) and have variable tissue distribution in the body. γδ T cells can perform complex functions, such as immune surveillance, immunoregulation, and effector function, without undergoing clonal expansion. Heterogeneous distribution and anatomic localization of γδ T cells in the normal and inflamed tissues play an important role in alloimmunity, autoimmunity, or immunity. The cross‐talk between γδ T cells and other immune cells and phenotypic and functional plasticity of γδ T cells have been given recent attention in the field of immunology. In this review, we discussed the cellular and molecular interaction of γδ T cells with other immune cells and its mechanism in the pathogenesis of various autoimmune diseases.